Enhancement of the Photodegradation Activity of Methylene Blue by the Low‐temperature Regulation of Oxide‐rich Graphitic Carbon Nitride. Issue 41 (3rd November 2021) - Xie, Kangle; Fang, Junfei; Li, Le; Deng, Jianping; Liang, Zhiyong
Abstract: Oxygen‐rich graphitic carbon nitride (OCN‐3) was synthesized by low‐temperature regulation after the chemical oxidation of g‐C3 N4, which was prepared by the calcination of melamine at a high temperature. Further, its photocatalytic activity was evaluated using methylene blue (MB) as the target pollutant for degradation. The characteristic results showed that OCN‐3 exhibited larger specific surface area (SSA) than pure g‐C3 N4 . Moreover, the recombination rate of its photogenerated carriers was significantly reduced. The photocatalytic degradation was performed with an MB solution that was prepared using ultrapure, tap, and lake water samples as the base liquids to measure the photocatalytic activity of OCN‐3. The experimental results display that the remove rate of MB has reached 83.7 %, 91.26 % and 95.2 %, respectively. The degradation of MB three consecutive times indicated that the catalyst exhibited good stability and reusability. Abstract : Oxygen‐rich graphitic carbon nitride (OCN‐3) was synthesized by low‐temperature regulation after the chemical oxidation of g‐C3 N4 . The OCN‐3 showed excellent photocatalytic performance on degradation of MB due to its larger specific surface area and lower recombination rate of photogenerated carriers than that of the pure g‐C3 N4 . The mechanism of the photocatalytic degradation of MB revealed that the active species which played the major role was h +, followed by . OH.